2024
DOI: 10.3389/fmicb.2024.1304325
|View full text |Cite
|
Sign up to set email alerts
|

A single point mutation in the Listeria monocytogenes ribosomal gene rpsU enables SigB activation independently of the stressosome and the anti-sigma factor antagonist RsbV

Xuchuan Ma,
Marcel H. Tempelaars,
Marcel H. Zwietering
et al.

Abstract: Microbial population heterogeneity leads to different stress responses and growth behavior of individual cells in a population. Previously, a point mutation in the rpsU gene (rpsUG50C) encoding ribosomal protein S21 was identified in a Listeria monocytogenes LO28 variant, which leads to increased multi-stress resistance and a reduced maximum specific growth rate. However, the underlying mechanisms of these phenotypic changes remain unknown. In L. monocytogenes, the alternative sigma factor SigB regulates the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 68 publications
0
1
0
Order By: Relevance
“…The signal of energy/nutritional stress enters the SigB activation pathway probably downstream from RsbU (Shin et al, 2010). Our recent study also showed that the SigB activation in RpsU 17Arg-Pro mutants is independent from the stressosome and the anti-sigma factor antagonist RsbV (Ma et al, 2024). It is conceivable that altered ribosomal function in the RpsU mutant results in poor growth performance, with the mechanisms underlying SigB activation and possible link to nutritional stress requiring further study.…”
Section: Discussionmentioning
confidence: 88%
“…The signal of energy/nutritional stress enters the SigB activation pathway probably downstream from RsbU (Shin et al, 2010). Our recent study also showed that the SigB activation in RpsU 17Arg-Pro mutants is independent from the stressosome and the anti-sigma factor antagonist RsbV (Ma et al, 2024). It is conceivable that altered ribosomal function in the RpsU mutant results in poor growth performance, with the mechanisms underlying SigB activation and possible link to nutritional stress requiring further study.…”
Section: Discussionmentioning
confidence: 88%